2021
DOI: 10.1128/spectrum.01376-21
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Three Quantitative Anti-SARS-CoV-2 Antibody Immunoassays

Abstract: The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) emerged in December 2019 and caused a dramatic pandemic. Serological assays are used to check for immunization and assess herd immunity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 36 publications
(42 reference statements)
3
20
0
Order By: Relevance
“…Whilst a nasopharyngeal swab (NPS) positivity [1,8] and seropositivity [4,12,18] similar to the present study was already reported elsewhere, some studies [15,16,36] found a higher risk of seropositivity for males or females [19]. In contrast with some studies [8,30,32,37] we found no association between age and risk of SARS-CoV-2 infection.…”
Section: Interpretation Of Findings In Relation To Other Studiessupporting
confidence: 85%
See 1 more Smart Citation
“…Whilst a nasopharyngeal swab (NPS) positivity [1,8] and seropositivity [4,12,18] similar to the present study was already reported elsewhere, some studies [15,16,36] found a higher risk of seropositivity for males or females [19]. In contrast with some studies [8,30,32,37] we found no association between age and risk of SARS-CoV-2 infection.…”
Section: Interpretation Of Findings In Relation To Other Studiessupporting
confidence: 85%
“…Sera were additionally tested with ELISA assay Wantai SARS-CoV-2 Ab ELISA (Beijing Wantai Biological Pharmacy Enterprise). Samples with a cutoff ratio (absorbance of the sample at 450 nm divided by 0.19) ≥1 AU/mL were considered positive [36].…”
Section: Methodsmentioning
confidence: 99%
“…SARS-CoV-2 IgG II Quant immunoassay detects all IgG antibodies against SARS-CoV-2, which includes neutralizing antibodies against the receptor binding domain (RBD) of the SARS-CoV-2 spike (S) protein, but are not exclusive to it. Chapuy-Regaud et al also report a moderate correlation (Spearman’s r = 0.63) between the results of SARS-CoV-2 IgG Quant immunoassay and live virus neutralization assays in known positive samples [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…We measured the antibody titers in 1,169 vaccinated individuals shortly before their breakthrough infection with the Omicron SARS-CoV-2 variant (1 November -31 December, 2021). Total SARS-CoV-2 antibodies were measured with a quantitative enzyme-linked immunosorbent assay (ELISA) (Wantai Biological Pharmacy Enterprise Co., Ltd, China) [5].…”
Section: Dear Editormentioning
confidence: 99%